LUCHINO VISCONTI’S PRIVATE LIBRARY AS A WAY TO UNDERSTAND THE CREATIVE BIOGRAPHY OF THE ARTIST - Ostrovskyi, Oleksandr (Ukrainian Cultural Studies, 2023)
The relevance of the research is due to the lack of research attention to the phenomenon of the artist’s private library which is both an influential and representative component of his/her creative work. The purpose of the article is to study the interconnections between the private library of the Italian theater and film director Luchino Visconti and his work. The main tasks were the systematization and analysis of the available descriptions of the director’s book collection. The approaches to the research of private libraries of other personalities were analyzed. The possibility of analyzing a private library without direct interaction with books-artifacts has been proven. Attention was paid to the idea of “reproducing” the artist’s personality in the books of one’s library. The impact on the personality of those books that could have been chosen by him/her, but remained unread, has been revealed. The importance of all, without exception, books stored in a private library is argued. The article proposes the method of systematization of L. Visconti’s private library collection by author, title, year of publication, impact of the text in his works, and topic. As a result of the research, quantitative indicators that were formed for each of the categories confirm or refute the director’s statements regarding certain influences on him. Identified significant replenishment of the library collection after 1944 coincides with the start of the director’s work in cinema and the final move to Italy. Since almost two-thirds of the library collection are devoted to theatre L. Visconti’s significant interest in theatrical topics has been identified. This deepens the idea of the theatricality of his thinking. The influence of some authors on the director’s work has been confirmed: in particular, the library has many books by W. Shakespeare and M. Proust, whose impact was mentioned by Italian director on many occasions in his interviews. Analysis of the library collection has shown L. Visconti’s interest in the theory and history of music and literature which allows researchers to unfold in his filmography the usage of the form-creating methods inherent to these arts. The conclusion is that a private library can be an important source to expand the researcher’s understanding of the artist’s creative biography. It is hypothesized that such a way of analysis and systematization can be applied to the research of creative biographies of other personalities.